A location, location, location mutation impairs DNM2-mediated release of nascent autophagosomes from recycling endosomes. Issue 7 (2nd July 2020) - Puri, Claudia; Rubinsztein, David C.
ABSTRACT: Elucidation of the membranes contributing to autophagosomes has been a critical question in the field, and an area of active research. Recently, we showed that key events in autophagosome formation, from PtdIns3P formation/WIPI2 recruitment to LC3-GABARAP membrane conjugation, occur on the RAB11A-positive compartment (recycling endosomes). This observation raised the question of how the LC3-positive autophagosome precursors detach from the recycling endosome. We recently observed that DNM2 (dynamin 2) mediates this step, and described how the DNM2 R465W mutation that causes centronuclear myopathy (CNM) leads to the accumulation of autophagic structures on recycling endosomes, thereby stalling macroautophagy/autophagy. This physiologically important step highlights the importance of understanding release of nascent autophagosomes from the recycling endosomes as part of the autophagy itinerary.